Atenção integral à mulher em situação de violência sexual nos serviços de saúde: Uma proposta de currículo para ensino a distância voltado aos profissionais de saúde em Unidades Hospitalares - Meire Rose de Oliveira Loureiro Cassini (2024)
Sexual violence is a public health, social and human rights problem. Recognized as one of the most serious types of violence, due to the resulting physical and emotional damage, it is characterized by any non-consensual sexual activity. It can result in death or disability, with a higher prevalence in women of reproductive age, resulting in mental and reproductive health problems. Coping with it requires coordination between the various existing devices, including health services. Understood as key strategies for caring for victims, health services must be organized and structured to provide comprehensive and resolute care to women. Given this scenario, the purpose of this study was to present a proposal for a course aimed at health professionals for comprehensive and humanized care for women in situations of sexual violence in hospital health services. The methodological path used a literature review and, to construct the course curriculum, Ten Cate's ten-step method was used for distance learning. The results were: 1) the development of a training course aimed at comprehensive care for women in situations of sexual violence in hospital health services and 2) the production of a review of the book “Sexual violence against women: approaches, contexts and challenges”, by Ludmila Fontenele Cavalcanti, published in 2022. The course was designed to have a total workload of 50 hours, distributed in 6 units covering interdisciplinary topics and knowledge, skills and attitudes relevant to intervention in the care of women victims of sexual violence. It was structured in a distance, asynchronous, self-instructional format, focused on active student learning and with a competency-oriented curriculum. The result related to the review will be presented in this volume in article format, in accordance with the standards of the journal to which it will be sent and the course description will be inserted in the results section. It is hoped that the implementation of the course, in the near future, will be able to provide tools to health professionals in the hospital context to deal with the issue of sexual violence and provide comprehensive and respectful care to victims.